Single-Shot Optical Multiple-Image Encryption Based on Polarization-Resolved Diffractive Imaging - Xiaoliang He; Hua Tao; Lijuan Zhang; Xiaodong Yuan; Cheng Liu; Jianqiang Zhu (IEEE Photonics Journal, 2019)
A new method for optical multiple-image encryption based on polarization-resolved diffraction imaging is proposed in this study. A linearly polarized beam is split into two beams of orthogonal polarization to illuminate different images to be encrypted, and these images are then encrypted into a single white-noise-like intensity image in a single shot. A multi-mode iterative phase-retrieval algorithm is used in the decryption to reconstruct the amplitudes and phases of the secret images simultaneously. Both computer simulations and optical experiments are performed to demonstrate the feasibility and effectiveness of the proposed method.